A fundamentalidade dos direitos sociais no estado democrático de direito - Coelho de Almeida, Dayse (Nómadas. Critical Journal of Social and Juridical Science, 2007)
This essay discusses the role of the Fundamental Rights opposed to the modern Constitutional Theory. Therefore, it is conceived that the social rights are fundamental rights, instigating a justified and grounded discussion upon the sheltered and chosen values of the Federal Constitution when founding the Legal Democratic State in Brazil. The article seeks to demonstrate the necessity of one constitutional hermeneutics well suited with the Brazilian reality as well as stimulator of the true democracy